Linking the Open Water Area of the North Open Water Polynya to Climatic Parameters using a Multiple Linear Regression Prediction Model. Issue 2 (15th March 2019) - April, André; Montpetit, Benoit; Langlois, Darlene
ABSTRACT: The North Open Water polynya is a recurring polynya and is a significant feature of northern Baffin Bay in the winter. An area of open water remains as the sea ice grows around it in the fall, and in the spring the polynya gradually expands as the thinner ice surrounding it melts. It is an important overwintering area for various bird and animal species. With climate change affecting the Arctic in particular, this polynya has seen significant transformation in terms of its area of open water. Our study analyzes this transformation and attempts to understand it by linking it to climatic parameters using a multiple regression model. Using data from ice analyses from Environment and Climate Change Canada's Canadian Ice Service, a significant difference in the annual maximum polynya extent was observed before and after 1998. The main climate indices related to the extent of the polynya for the years prior to 1998 are surface wind speed and sea-ice concentration. For the years after 1998, the main indices are surface wind speed, sea surface temperature, and surface air temperature. This study indicates that the extent of open water in the polynya could be a good indicator of a new climate regime after 1998.